An Insight into Processing and Properties of Smart Carbon Nanotubes Reinforced Nanocomposites. Issue 1 (2nd January 2022) - Kanu, Nand Jee; Bapat, Saurabh; Deodhar, Harshad; Gupta, Eva; Singh, Gyanendra Kumar; Vates, Umesh Kumar; Verma, Girish C.; Pandey, Vivek
ABSTRACT: Years after the discovery of graphene and carbon nanotubes (CNTs) mechanical engineers, scientists have been figuring out various ways to incorporate these with the resin without forcing the companies to reinvent their production processes. As a result, CNTs are now progressing in aerospace as well as high-performance sports equipment and into the bodies of boats, cars and planes. CNT reinforced composite material is light as well as strong and using proper shape and various types of CNTs, we can improve mechanical properties. Thus, there is a need to analyze and compare the methods, which are used to manufacture these smart materials. Through this review article different methods of CNT reinforced composites have been compared on account of their applications, time for preparation, cost of fabrication, matrix element, mechanical, electrical, chemical properties enhancement, etc. Various manufacturing methods such as cross-linked polymerization, electrochemical co-deposition, resin film infusion, vacuum assisted resin transfer molding, etc., have been covered in this review article. It is believed that this will broaden the perspective while choosing the optimum method to be used in future applications. Graphical abstract: uf0001